1983
DOI: 10.1104/pp.73.3.698
|View full text |Cite
|
Sign up to set email alerts
|

Release of Calcium from Suspension-Cultured Glycine max Cells by Chitosan, Other Polycations, and Polyamines in Relation to Effects on Membrane Permeability

Abstract: Treatment with chitosan of suspension-cultured Glycine max cells labeled with 45Ca2" caused a rapid release of calcium, which was complete much earlier than the chitosan-induced leakage of intracellular electrolytes and probably reflects calcium loss primarily from the cell wall and/ or plasma membrane. A linear correlation was found between calcium release from chitosan-treated whole cells or isolated cell walls and the amount of chitosan bound. Other polycations (poly-L-lysine, histone, DEAE-dextran, and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
77
0
3

Year Published

1992
1992
2017
2017

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 149 publications
(82 citation statements)
references
References 9 publications
2
77
0
3
Order By: Relevance
“…This is also in agreement with an earlier report in which chitosan is shown to displace calcium ions from isolated cell walls of Glycine max suspension cultures (Young & Kauss, 1983). Deacetylated chitosans but not chitin are present on the surface of the cell walls of fungal infection structures growing in planta after pathogens such as Puccinia graminis, Uromyces fabae or Colletotrichum lindemuthianum have invaded their hosts (El Gueddari et al, 2002).…”
Section: Perception Of Chitosaccharides By Plant Cellsupporting
confidence: 81%
“…This is also in agreement with an earlier report in which chitosan is shown to displace calcium ions from isolated cell walls of Glycine max suspension cultures (Young & Kauss, 1983). Deacetylated chitosans but not chitin are present on the surface of the cell walls of fungal infection structures growing in planta after pathogens such as Puccinia graminis, Uromyces fabae or Colletotrichum lindemuthianum have invaded their hosts (El Gueddari et al, 2002).…”
Section: Perception Of Chitosaccharides By Plant Cellsupporting
confidence: 81%
“…Using a similar approach Young and Kauss [17] found that PLLs increase cell membrane permeability with increasing PLL length.…”
Section: Introductionmentioning
confidence: 98%
“…Raafat et al [16] stated that in spite of been accepted as a possible mechanism, the probability of it occurring is Three models have been proposed, the most acceptable being the interaction between positively charged chitin/ chitosan molecules and negatively charged microbial cell membranes. In this model the interaction is mediated by the electrostatic forces between the protonated NH + 3 groups and the negative residues [17] , presumably by competing with Ca 2+ for electronegative sites on the membrane surface [18] . This electrostatic interaction results in twofold interference: i) by promoting changes in the properties of membrane wall permeability, thus provoke internal osmotic imbalances and consequently inhibit the growth of microorganisms [10,12] , and ii) by the hydrolysis of the peptidoglycans in the microorganism wall, leading to the leakage of intracellular electrolytes such as potassium ions and other low molecular weight proteinaceous constituents (e.g.…”
Section: Introductionmentioning
confidence: 99%